The inflation target and the equilibrium real rate - Christopher D. Cotton (Federal Reserve Bank of Boston, 2020)
Many economists have proposed raising the inflation target to reduce the probability of hitting the zero lower bound (ZLB). It is both a common assumption and a feature of standard models that raising the inflation target does not impact the equilibrium real rate. I demonstrate that in the New Keynesian model, once heterogeneity is introduced, raising the inflation target causes the equilibrium real rate to fall. This implies that raising the inflation target will increase the nominal interest rate by less than expected and thus will be less effective in reducing the probability of hitting the ZLB. The channel involves a rise in the inflation target lowering the average markup by price rigidities and a fall in the average markup lowering the equilibrium real rate by household heterogeneity, which could come from overlapping generations or idiosyncratic labor shocks. I find that raising the inflation target from 2 percent to 4 percent lowers the equilibrium real rate between 3 and 28 basis points. Since raising inflation lowers the equilibrium real rate, it might seem optimal to raise inflation by more in response to the ZLB. However, this channel also implies that the marginal benefit of raising inflation is lower because a given increase in inflation raises the nominal interest rate by less and thus is less effective at preventing the ZLB. In a welfare simulation, these two effects approximately cancel out each other. Therefore, even though this channel implies that raising the inflation target is less effective in preventing the ZLB, the inflation target should still be raised by a similar amount in response to the problem of the ZLB.
Keywords: E31; E52; E58; 330; inflation target; steady state real interest rate; equilibrium real rate; heterogeneity; zero lower bound